2013
DOI: 10.1682/jrrd.2012.02.0027
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of robotic-assisted tilt-table therapy for early-stage spinal cord injury rehabilitation

Abstract: Abstract-Damage to the spinal cord compromises motor function and sensation below the level of injury, resulting in paralysis and progressive secondary health complications. Inactivity and reduced energy requirements result in reduced cardiopulmonary fitness and an increased risk of coronary heart disease and cardiovascular complications. These risks may be minimized through regular physical activity. It is proposed that such activity should begin at the earliest possible time point after injury, before extens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…Higher pain threshold, and therefore, higher FES intensities might not be an issue for some patients, for example, in individuals with complete paralysis. However, in comparison with healthy subjects, in such patients, with FES, less muscle force could be available due to inadequate muscle recruitment as a result of muscle atrophy in paralyzed limbs (Riener and Fuhr, 1998; Craven et al, 2013). Therefore, similar to healthy subjects, we do not expect that in these patients PE effect with higher FES intensities would be significantly different from PE effect with minimum FES I MIN .…”
Section: Discussionmentioning
confidence: 99%
“…Higher pain threshold, and therefore, higher FES intensities might not be an issue for some patients, for example, in individuals with complete paralysis. However, in comparison with healthy subjects, in such patients, with FES, less muscle force could be available due to inadequate muscle recruitment as a result of muscle atrophy in paralyzed limbs (Riener and Fuhr, 1998; Craven et al, 2013). Therefore, similar to healthy subjects, we do not expect that in these patients PE effect with higher FES intensities would be significantly different from PE effect with minimum FES I MIN .…”
Section: Discussionmentioning
confidence: 99%
“…Since our investigation (Sarabadani Tafreshi et al, 2016) and furthermore, other patient studies investigating deployment of FES together with PE (Chi et al, 2008; Craven et al, 2013; Kuznetsov et al, 2013; Yoshida et al, 2013) had found no significant contribution from the FES to the PE effect, in the current study, we omitted investigation of the FES effect. Instead, we investigated whether changing the PE frequency (i.e., stepping speed) influences the PE effect [see Hypothesis (b) above].…”
Section: Introductionmentioning
confidence: 77%
“…As a potential solution for safe mobilization, a robot-assisted tilt table has been suggested (Colombo et al, 2005). Feasibility in early rehabilitation of patients with neurological disorders was demonstrated (Craven et al, 2013; Kuznetsov et al, 2013; Frazzitta et al, 2015). In contrast to conventional tilt tables, robot-assisted tilt tables (Erigo, Hocoma AG, Switzerland) have an integrated robotic module, which allows passive robotic leg exercise (PE) training (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to improving orthostatic tolerance, robotic tilttable may also be an effective exercise tool in initiating the rehabilitation process at the earliest possible time point after stroke may minimize the reduction in aerobic fitness that occurs due to inactivity. It was also found that robotic tilt-table can be used to provide a strong training stimulus to complement conventional physiotherapy practices and serve the dual purpose of increasing orthostatic tolerance and attenuating the decline in aerobic fitness [41]. Although MMSE and muscle strength of the upper limb in both the groups improved equally, the other parameters improved more after tilt-table exercises.…”
Section: Discussionmentioning
confidence: 96%